The knowledge of teachers as a key factor in providing first aid in primary schools - Kovačič, Uroš (Array, 2019)
Background: In addition to home, school is the second most important living environment in a child’s life. Injuries that most often occur in school and on the school playground are the primary cause for the death of children. In case of sudden health problems in schools, teachers are usually the first to be at a child’s side. We were interested in how well teachers in primary schools are familiar with first aid measures in selected health cases. Methods: Collecting of data in the framework of the descriptive method of research was conducted with an anonymous survey questionnaire using the online program 1ka. One hundred and ninety-two teachers filled in the survey questionnaire in its entirety. Results: Teachers have a lack of theoretical knowledge of first aid in life-threatening situations. In four of the nine questions on the selected first aid measures, the teachers who teach at the upper level of primary school showed statistically significantly poorer knowledge compared to the teachers who teach at the lower level of primary school. Conclusions: Teachers at the lower level who teach in the early stage of the education system displayed better theoretical knowledge of first aid. This may be the result of a difference in their educational role during the schooling of an individual pupil. While a lower-level teacher who is associating with the particular pupil all day long is involved in the general education of the pupil, the teacher at a higher-level teaches a specific subject and only has contact with a certain pupil a few hours a week. Theoretical knowledge is only a basic prerequisite for performing first aid, practical skills are required as well. It is essential that teachers in primary school renew and upgrade their knowledge of first aid, as doctrinal guidance changes and first aid knowledge is also forgotten. If teachers are responsible for the practical performance of first aid measures on an injured or suddenly ill child, the school pri